Cytomegalovirus Infection May Contribute to the Reduced Immune Function, Growth, Development, and Health of HIV-Exposed, Uninfected African Children - Filteau, Suzanne; Rowland-Jones, Sarah (Frontiers in Immunology, 2016)
With increasing access to antiretroviral therapy (ART) in Africa, most children born to HIV-infected mothers are not themselves HIV-infected. These HIV-exposed, uninfected (HEU) children are at increased risk of mortality and have immune, growth, development, and health deficits compared to HIV-unexposed children. HEU children are known to be at higher risk than HIV-unexposed children of acquiring cytomegalovirus (CMV) infection in early life. This risk is largely unaffected by ART and is increased by breastfeeding, which itself is critically important for child health and survival. Early CMV infection, namely in utero or during early infancy may contribute to reduced growth, altered or impaired immune functions, and sensory and cognitive deficits. We review the evidence that CMV may be responsible for the health impairments of HEU children. There are currently no ideal safe and effective interventions to reduce post-natal CMV infection. If a clinical trial showed proof of the principle that decreasing early CMV infection improved health and development of HEU children, this could provide the impetus needed for the development of better interventions to improve the health of this vulnerable population.